IMPACT OF ISLAMIC FINANCING ON INCREASING WELFARE OF UMKM IN SOUTH SULAWESI - Ince Nurul Sakhinah R; Nur Wahyuni; Zainal Abidin; Kamaruddin Kamaruddin (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
This study examines the impact of Islamic financing on the enhancement of equality for Micro, Small, and Medium Enterprises (MSMEs) in South Sulawesi. As one of the regions with a growing number of MSMEs, South Sulawesi has seen an increasing interest in Islamic financial products as an alternative source of capital. The research aims to evaluate how Islamic financing contributes to the economic empowerment of MSMEs, especially in addressing inequality in access to financial resources. Data was collected through surveys distributed to MSME owners in various sectors in South Sulawesi, focusing on their experiences with Islamic financing institutions. The results indicate that Islamic financing has significantly improved the access of MSMEs to capital, which in turn has fostered better financial inclusion and equal opportunities for business growth. The study highlights key factors such as the compliance of Islamic financial products with local values, the ease of accessing financing, and the role of Islamic banks in supporting MSMEs. These findings suggest that Islamic financing can be an effective tool in promoting economic equality and improving the sustainability of MSMEs in South Sulawesi.